DISCIPLINE “PRINCIPLES OF EXTERNAL ADVERTISEMENT” IN THE ART PEDAGOGICAL EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
In article is considered the questions of the role and place of the discipline “Principles of external advertisement” in the learning process of HLL. Author presents a tentative programme for her teaching in the block of discipline of the specialty. “Fine Art. Design of advertisement” in the art-graphic department of Krivy Rig pedagogical university.